Therapeutic semi-safe space in group analysis. (June 2019) - Berman, Avi
People come to group analysis knowing that the group is not completely safe. They choose to join an unknown, and in many respects unpredictable and challenging, interpersonal environment. 'Semi-Safe space' in group analysis is a co-created, basically safe and mutually accepted infrastructure, with the mutually recognized challenge of being and communicating in an unexpected and not fully protected environment. The group's semi-safe space represents one of the main advantages of group psychotherapy if handled professionally. Group analysis is a potential space in which minds may be created and develop through mutual interaction, which is sometimes inevitably turbulent and experienced as unsafe. On the other hand, excessive 'unsafety' might destroy the boundaries of the psychotherapeutic domain and become harmful or even traumatic. It is the conductor's crucial responsibility to create initial safety in the group. He can contribute to the participants' sense of safety by exercising some authority in stating those boundaries and opposing any deviation from them. This contract is based on reciprocity and exchange: protecting the safety of one participant in the group is equivalent to protecting the safety of the others. Mutual risk-taking produces safety while its lack intensifies doubt and fear.